Analisis Penentuan Kualitas Aset Produktif (KAP) dan Penyisihan Penghapusan Aset Produktif (PPAP) berdasarkan POJK 33 Tahun 2018 pada PT BPR Suryajaya Kubutambahan - Safitri, Nabila; Atmadja, Anantawikrama Tungga (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the determination of Earning Assets Quality (KAP) and the calculation of Allowance for Earning Assets Losses (PPAP) at PT. BPR Suryajaya Kubutambahan. This research was conducted using a qualitative descriptive method, where the researcher will conduct direct observations in the field and collect data to be analyzed based on the observations and knowledge of the researcher. This research was conducted at PT. BPR Suryajaya Kubutambahan, having its address at Jalan Raya Kubutambahan. Sources of data in this study consisted of primary data and secondary data. Methods of data collection in this study using interviews, documentation, and literature study. This study uses data analysis consisting of data collection, data reduction, data presentation, data analysis and drawing conclusions. The results of the study stated that BPR Suryajaya Kubutambahan has determined the quality of earning assets for loans and placements with other banks with reference to the Financial Services Authority Regulation (POJK) 33 of 2018. In the formation of PPAP, BPR Suryajaya Kubutambahan has formed in accordance with the percentages listed on regulations and also considers the value of the collateral submitted by the debtor to the BPR